Investigação molecular e epidemiológica de genes do metabolismo de xenobióticos em pacientes com câncer colorretal esporádico - Fernandes, Glaucia Maria de Mendonça (2013)
Introduction: The xenobiotics are exogenous substances to the organism, as N-nitrosamines, heterocyclic amines (HAs) and polycyclic aromatic hydrocarbons (PAHs), can which result in DNA adducts formation. Polymorphisms in genes involved in the metabolism of xenobiotics could contribute to this process and modulate the development of cancer. Objectives: To investigate the CYP1A1*2A (rs4646903), CYP1A1*2C (rs1048943), CYP2E1*5B (rs2031920), CYP1E1*6 (rs6413432), Tyr113His EPHX1 (rs1051740) and His139Arg EPHX1 (rs2234922) polymorphisms related to the metabolism of xenobiotics, the risk of sporadic colorectal (SCRC) cancer, the interaction of these polymorphisms with lifestyle (smoking and drinking) and clinical and histopathological parameters and to evaluate the association of SCRC with socio-demographic factors. Methods: A case-control study was conducted in 641 subjects in the Brazilian population (241 patients with colorectal cancer and 400 controls (individuals without a history of cancer). Real-Time PCR and PCR-RFLP was performed for genotyping. Statistical analysis was performed using the chi-square tet and multiple logistic regression binary. Results: The results showed statistically significant differences between the case and control groups for age greater than 50 years (OR=8.21, 95%CI=5.49-12.28, p<0.01) and male gender (OR=0.50, 95%CI=0.32-0.87, p<0.01) The analysis of polymorphisms revealed an association between the alleles polymorphic CYP2E1*5B (OR=2.84, 95%CI=1.78-4.52, p<0.01, additive model) and CYP2E1*6 (OR=2.78, 95%CI=1.91-4.06, p<0.01, additive model) and the SCRC. Tumor size, lymph node involvement and disease primary site were not associated with polymorphisms. Conclusion: The CYP2E1*5B and CYP2E1*6 polymorphisms are involved in the risk of SCRC and individuals with age ≥ 50 years are more susceptible to this tumor type, of males are less susceptible.